A review of antioxidant potential from seaweeds - extraction, characterization, benefits and applications - Nazirah, M; Evangeline Yvonne. S; Mohd Hafiz, A.M; Mohd Sani, S. (Food Research, 2023)
Potential natural antioxidant from seaweeds is used to improve the oxidative stability of food. It also functions as an active ingredient. There are three classes of antioxidants consisting of vitamins, carotenoids and polyphenols. Researchers employ a variety of ways to evaluate antioxidant activity, including screening approaches and chemical composition. Solid-liquid extraction pressured liquid extraction, supercritical fluid extraction, and other green extraction techniques are among the seaweed antioxidant extraction methods commonly utilized and reviewed in this article. The aim of the review was to identify the potential source of high antioxidant content and polysaccharides, along with the best extraction method. This overview summarised the composition of seaweed antioxidants, extraction methods and the advantages of antioxidants found in seaweed.